Rancang Bangun Sistem Pendeteksi Ketinggian Bahan Bakar pada HFO Settling Tank Berbasis IoT di MT. Quantum Harmony - Reyhan Batara Victorrahman; Agus Dwi Santoso; Elly Kusumawati; Akhmad Kasan Gupron (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research aims to design a HFO Settling Tank monitoring simulation tool using an ultrasonic sensor that displays the fuel level in real time and accurately. The research that will be carried out is by utilizing Arduino Uno microcontroller technology and utilizing ultrasonic waves from ultrasonic sensors to determine a height in a tube container. These sensors as inputs will be received by Arduino Uno and the data results from the sensor will be displayed on the LCD and notification from the buzzer. In this study the authors used a research method in the form of the Rnd (Research and Development) method, which begins by analyzing and conducting in-depth research on an object or tool. Then the author designs a tool design which will then validate the design design, and revise the product if the design is deemed insufficient. For the last stage, testing the product, if the tool does not work according to the expected function, a redesign will be carried out. The result of this research is that the ultrasonic sensor is able to detect the height of the simulated container. The results of the detection are processed through Arduino and displayed on the LCD so that all parties can know the water level in the tube container.